Product Development Priorities in Modest Fashion: Insights from Kano Model Analysis - Oktaviani, Devi Nurmifta; Riandi, Muhammad Hafiz (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to identify the product attributes that most influence customer satisfaction and purchasing decisions and to provide recommendations for improving Muslimah dress products at Nym Collection using the Kano model and a product quality approach. Design/Methodology/Approach – A quantitative survey design was employed. Data were collected through a questionnaire using a five-point Kano evaluation scale comprising 10 functional and 10 dysfunctional questions representing 10 product attributes. The population consisted of 250 customers who had purchased Muslimah dresses within the previous six months. Using the Slovin formula and random sampling, 154 respondents were selected. Instrument validity and reliability were tested, and the data were analyzed using the Kano model to classify product attributes based on their impact on customer satisfaction. Findings – The results indicate that four attributes are classified as One-dimensional: the latest dress models, unique and attractive designs, a wide variety of dress models, and high-quality stitching. These attributes have the greatest influence on customer satisfaction and should be prioritized for product development. The remaining six attributes are classified as Indifferent, indicating that they have relatively little impact on customer satisfaction. The Kano satisfaction graph further confirms that emphasizing One-dimensional attributes can enhance customer satisfaction and strengthen the competitiveness of Nym Collection in the Muslimah fashion market. Originality/Value This research offers originality by applying the Kano model specifically to Muslimah dress products, a segment that is still limited in empirical studies. The findings provide practical value by guiding fashion businesses in prioritizing product attributes that most effectively increase customer satisfaction and market competitiveness.